Aspectos instigantes do sindicalismo na contemporaneidade: liberdade, solidariedade e crise / Instigating aspects of contemporary trade unionism: freedom, solidarity and crisis - Valadão, Carla Cirino; Reis, Ítalo Moreira (Revista do Programa de Pós-Graduação em Direito, 2015)
The purpose of this article is to discuss the current union model crisis. For this, we must discuss the changes experienced in society, from the solid modern times until the liquid modernity. It is also necessary to discuss the new types of labors and as collective entities work deal with the current reality. Even to discuss, freedom of association in the national context, to the extent that the absence of effective freedom is one of the causes for the crisis faced by trade unions. It is intended to also analyze other factors contributing to the lack of representation and mitigating the sense of solidarity among workers.